Incremental Value of Live/Real Time Three‐Dimensional Transthoracic Echocardiography over Two‐Dimensional Echocardiography in Hypertrophic Cardiomyopathy with Mid‐Ventricular Obstruction and Apical Aneurysm. Issue 3 (24th November 2014) - Thind, Munveer; Joson, Marisa; Gaba, Saurabh; Elsayed, Mahmoud; Bulur, Serkan; Guvenc, Tolga; Elguindy, Mostafa; Nanda, Navin C.
<x xml:space="preserve">Abstract</x> We describe a case of hypertrophic cardiomyopathy with mid‐left ventricular obstruction and apical aneurysm containing thrombi where live/real time three‐dimensional transthoracic echocardiography provided incremental value over two‐dimensional echocardiography in assessing the findings.